Issues in the Distribution of Inheritance Within Families: A Study in Sidokerto Village, Mojowarno District, Jombang Regency - Kuswanto, Kuswanto; sugiana, sugiana; Andri, Muhammad (Scholar Center, 2025)
Inheritance distribution within families often triggers conflicts, particularly when differing legal principles intersect, such as customary law and Islamic law. This study investigates the inheritance distribution mechanism in Sidokerto Village, Mojowarno District, Jombang Regency, focusing on the tension between customary law, which promotes equal distribution among heirs, and Islamic law, which applies a 2:1 ratio favoring male heirs. The research aims to identify the dominant factors influencing these inheritance patterns, including local traditions, legal awareness, and the socio-economic background of heirs.Using an empirical-juridical approach, the study combines a statute approach (analysis of legal texts), a case approach (review of inheritance-related disputes), and a sociological approach (examination of social practices). Primary data were collected through interviews with the village head and community leaders, while secondary data included national inheritance laws, the Compilation of Islamic Law, the Quran, and scholarly literature on inheritance practices. Findings reveal that most of the Sidokerto Village community adheres to customary inheritance law, emphasizing equal rights among heirs regardless of gender. However, a smaller portion of the population follows Islamic inheritance principles. This divergence often leads to disputes, especially when family members have differing interpretations of applicable legal norms. Factors influencing inheritance decisions include long-standing local customs, varying levels of legal knowledge, and the economic status of heirs. In most cases, inheritance issues are resolved through family deliberation, often mediated by village officials. The inheritance process typically begins with asset inventory and heir identification, serving as the foundation for distribution decisions.